2018
DOI: 10.3389/fpubh.2018.00015
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Adolescent Self-Awareness and Accuracy Using a Performance-Based Assessment and Parental Report

Abstract: AimThe aim of this study was to assess awareness of performance and performance accuracy for a task that requires executive functions (EF), among healthy adolescents and to compare their performance to their parent’s ratings.MethodParticipants: 109 healthy adolescents (mean age 15.2 ± 1.86 years) completed the Weekly Calendar Planning Activity (WCPA). The discrepancy between self-estimated and actual performance was used to measure the level of awareness. The participants were divided into high and low accurac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
1
17
1
Order By: Relevance
“…Self-awareness develops throughout childhood and adolescence, and studies have indicated that there are developmental differences in self-awareness and stress appraisal, with most adolescents' evaluation of their emotional status tending to be less accurate than an adult's self-evaluation. 24,25 In addition, it has been suggested that parent-child agreement on child quality of life may be influenced by factors such as the child's health status, the domains assessed, and the parent's own mental health and quality of life. 26 Although the discrepancy between parent and patient report may be expected, it may also have important implications related to the child's participation in physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Self-awareness develops throughout childhood and adolescence, and studies have indicated that there are developmental differences in self-awareness and stress appraisal, with most adolescents' evaluation of their emotional status tending to be less accurate than an adult's self-evaluation. 24,25 In addition, it has been suggested that parent-child agreement on child quality of life may be influenced by factors such as the child's health status, the domains assessed, and the parent's own mental health and quality of life. 26 Although the discrepancy between parent and patient report may be expected, it may also have important implications related to the child's participation in physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…We found that adolescents and young adults reported much higher self-control before and after treatment than the therapists. An explanation could be that adolescents and young adults with impulse control problems overestimate their EF ability (52) and that adolescents with lower EF scores show less self-awareness (53). Also, they may show more social desirable responding before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…After users confirm their plan, they are asked to self-rate their self-created plan on a five-star scale, specifically rating their own performance and evaluating the effectiveness of their choices [23]. A sample of a finalized plan is shown in Figure 3.…”
Section: Mobile Applicationmentioning
confidence: 99%
“…A cardinal constituent of the strategy-acquiring process is the person's self-awareness of performance. This reflects the relationship between knowledge, beliefs, the particular task's demands, and the specific context of the task to identify errors or less effective strategies and correct them both during and after completing the task [23]. These strategies and skills are vital when coping with new challenges in daily life, and relationships between such cognitive skills and health behaviors while taking part in various food-related activities among adolescents with CD have been found [21].…”
Section: Introductionmentioning
confidence: 99%